New for Ukraine representatives of the genera Bolbitius and Conocybe (Bolbitiaceae, Basidiomycota) - Prydiuk M.P. (Ukrainian Botanical Journal)
The article provides data about finds of some new and rare for Ukraine taxa of the genera Bolbitius and Conocybe. Two species, Conocybe ambigua and C. rickenii, and one variety, Bolbitius titubans var. olivaceus, were found for the first time in Ukraine, while for four species (Conocybe macrocephala, C. macrospora, C. subpallida, and C. subpubescens) and one variety, Conocybe subxerophytica var. brunnea, new localities were recorded. The distribution data in Ukraine and worldwide are presented for all reported taxa. For the new in the country species and varieties, their descriptions and original drawings of the macro- and microscopic features are also provided.